Features of Educational Motivation and Emotional Attitude to Learning of 4-grade Students (on the Example of Traditional and Developmental Education) - Voronkova I.V; Lagutina E.N; Adaskina A.A (Moscow State University of Psychology and Education, 2022)
The article presents the results of a study of educational motivation and emotional experiences of junior schoolchildren studying in different didactic systems (N=54). It was revealed what motives are leading among students of the 4th grade and whether there are differences in the emotional attitude to learning between children studying in different educational programs. The research used the following methods: observation of the teacher and students in the classroom, conversation with students, M.V. Matyukhina "Diagnostics of the structure of educational motivation of a schoolchild", Methodology for diagnosing motivation for learning and emotional attitude to learning (A.D. Andreeva). It was revealed that for fourth-graders, regardless of the educational program, one of the leading motives is the motive of self-improvement and self-education. For students according to the Elkonin-Davydov system, educational and cognitive motives are also leading, and for schoolchildren of the traditional system, the motives of duty and responsibility and avoiding trouble. Younger schoolchildren studying according to the Elkonin-Davydov educational system demonstrate a more positive emotional attitude to learning.